2018
DOI: 10.3389/fpls.2018.00813
|View full text |Cite
|
Sign up to set email alerts
|

A Growth-Promoting Bacteria, Paenibacillus yonginensis DCY84T Enhanced Salt Stress Tolerance by Activating Defense-Related Systems in Panax ginseng

Abstract: Panax ginseng (C.A. Mayer) is a well-known medicinal plant used in traditional medicine in Korea that experiences serious salinity stress related to weather changes or incorrect fertilizer application. In ginseng, the use of Paenibacillus yonginensis DCY84T to improve salt stress tolerance has not been thoroughly explored. Therefore, we studied the role of P. yonginensis DCY84T under short-term and long-term salinity stress conditions in a controlled environment. In vitro testing of DCY84T revealed high indole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 80 publications
(86 reference statements)
2
38
0
Order By: Relevance
“…Four POD isoforms, two SOD isoforms, and four PPO isoforms with different molecular weights were significantly up-regulated in tomato plant roots inoculated with BHU-AV3 compared to un-inoculated plants under salt stress. The expression of multiple isoforms of antioxidant enzymes is involved in reducing the content of ROS and preventing the cell-damage (Kim et al, 2005;Zhang et al, 2013;Vighi et al, 2017;Arora and Bhatla, 2017;Sukweenadhi et al, 2018). In one study, new POD and SOD isoforms were expressed in response to salt stress tolerance in potato plants (Rahnama and Ebrahimzadeh, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Four POD isoforms, two SOD isoforms, and four PPO isoforms with different molecular weights were significantly up-regulated in tomato plant roots inoculated with BHU-AV3 compared to un-inoculated plants under salt stress. The expression of multiple isoforms of antioxidant enzymes is involved in reducing the content of ROS and preventing the cell-damage (Kim et al, 2005;Zhang et al, 2013;Vighi et al, 2017;Arora and Bhatla, 2017;Sukweenadhi et al, 2018). In one study, new POD and SOD isoforms were expressed in response to salt stress tolerance in potato plants (Rahnama and Ebrahimzadeh, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that different mechanisms are involved in each bacterial/plant interaction that leads to plant growth stimulation under saline conditions, and that a bacterial strain that stimulates growth of one plant species in the presence of salt may not cause similar stimulation in other plants. Some examples include ginseng, where Paenibacillus yonginensis strain DCY84 T protects against salinity stress by induction of defense related systems including ion transport, ROS enzyme production, proline content, total sugar and ABA biosynthesis related genes (Sukweenadhi et al, 2018). Another research group found that an endophytic strain of Bacilllus amyloliquefaciens produces ABA in response to increasing salinity, increasing production of glutamic acid and proline to increase resistance to salinity in rice (Shahzad et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…UPMR18) enhanced the levels of SOD, APX, and CAT and triggered the regulation of genes involved in ROS pathway (CAT, APX, GR, and DHAR) in okra plants under salinity stress [31] . Priming of Panax ginseng with salt-tolerant Paenibacillus yonginensis DCY84 T facilitated the expression of various antioxidant genes such as PgAPX and PgCAT, increasing the plant tolerance against salinity stress [83] . Along with enzymatic ROS scavenging, HT-PGPR also produce non-enzymatic antioxidants such as ascorbate (AsA), carotenoids, tocopherols, glutathione (GSH) and phenolics which act as defense molecules for the plant under saline conditions [84] .…”
Section: Ht-pgpr Mediated Salt Tolerance In Plantsmentioning
confidence: 99%